Prospects for the Development of Mountain Tourism in Azerbaijan - Almasov Nahid; Orujov Elshan (BIO Web of Conferences)
Mountain tourism in Azerbaijan has significant potential for development, given the country’s diverse landscapes, rich cultural heritage and emerging tourism infrastructure. The Greater and Lesser Caucasus Mountains offer unique opportunities for ecotourism, adventure tourism and winter sports, making Azerbaijan a promising destination for mountain lovers. This article examines the future prospects for mountain tourism in Azerbaijan, focusing on key factors such as infrastructure development, environmental sustainability and the promotion of local culture. Key initiatives include expanding facilities in popular destinations such as Shahdag and Tufandag resorts, improving road and transport networks and enhancing the quality of accommodation and services. In addition, promoting sustainable tourism practices to preserve the natural environment and engage local communities is crucial. Azerbaijan’s strategic location between Europe and Asia and its visa facilitation programmes offer great potential for attracting foreign tourists. The article also examines challenges such as the need for trained specialists, seasonal restrictions and competition with neighbouring countries. By investing in infrastructure, promoting responsible tourism and utilizing its unique natural resources, Azerbaijan can establish itself as a top mountain tourism destination, contributing to regional development and economic diversification.